One for all: The ECB's inflation target - Henning Weber (Kiel Institute for the World Economy (IfW), 2012)
The ongoing sovereign debt crisis and the manifold attempts to resolve it imply the possibility that inflation rates in countries of the euro area will differ from one another for an extended period of time. For instance, some propose that the North should accept inflation rates above the euro-area average to ease the burden of adjustment in the South. In order to understand better some of the welfare consequences of proposals like this one, this note looks into what rate of inflation a central bank should target in a monetary union and what determines a region's weight in this target.
Keywords: 330